Postpamćenje u romanu Sofije Andruhovyč Amadoka : neizrecivost povijesnih traume vs. terapeutska naracija - Ğrebenjuk, Tetjana; Гребенюк, Тетяна Володимирівна (My University, 2021)
The novel Amadoka (2020) by a Ukrainian writer Sofia Andruhovych is considered in the article as an experiment with postmemory ‡ the notion introduced by Marianne Hirsch meaning “relationship of the second generation to powerful, often traumatic, experiences that preceded their births”. Specifically, the Amadoka narrative in the context of the theory of postmemory considers the tension between unspeakability of traumatic experience and the characters’ need to speak it out in order to turn away from the traumatic past. In the focus of attention is also narrativization of historical traumas as a means of creation of false memories.
Postmemory in sofia andruhovych’s novel amadoka: unspeakable historical traumas vs. therapeutic narration
Keywords: Sofia Andruhovych; the novel Amadoka; historical trauma; postmemory; unspeakability; narration